Barriers to Exclusive Breastfeeding in Mothers Belonging to Low, Middle, and High Socio-Economic Families in Pakistan - Khan, Sabeen Abid; Ali, Naurin; Maroof, Fatima; Fatima Hussain, Syeda Namayah (International Journal of Child Health and Nutrition, 2023)
Introduction: Exclusive breastfeeding (EBF) for the first six months of life improves health and increases infant survival. In Asia, Pakistan ranks second in child mortality. Socioeconomic status (SES) is an important predictor of healthy behaviors. The study aims to understand the barriers to exclusive breastfeeding faced by mothers from different socioeconomic classes in Pakistan. Method: The cross-sectional study was done in the Pediatric outpatient department (OPD) of Shifa International hospital and community health center from November 2020 to 1 March 2021. Mothers and their children 1 to 3 years of age were included in the study. Results: A total of 175 mothers and their children were included. EBF for the first six months was done by 120 (68.6%). However, by one year of age, only 99 (56%) continued breastfeeding. Out of these 175 mothers, 79 (45%) were from the lower class, 69 (39.4%) were from the middle class, and 27 (15.4%) were from upper SES. Among the lower, middle, and high socioeconomic classes frequency of EBF practiced by mothers was 51, 54, and 15 (p 0.03), respectively. Pre-lacteals were given to 102 (58.2%). This practice was more frequent in lower SES families (0.03). The majority of working women belonged to upper SES (0.04). Mothers in the upper class are least likely to EBF their children (OR 0.5 CI 0.2-1.3). The adjusted odds ratio for EBF is highest for lower SES mothers, followed by the middle class. Conclusion: Support from family, place and mode of delivery, working mothers, and high socioeconomic class are important factors affecting exclusive breastfeeding in Pakistan.